Assessment of the Effect of Breast Size on Dose Distribution for 3Dand Conventional Methods with TLD Dosimetry in Breast Phantoms - Mahdieh Afkhami-Ardakani; Mahbood Esfahani; Yalda Nourollahi; Yaghub Ashuri-Taziyani; Mohamad Hagh-Parast (Frontiers in Biomedical Technologies, 2015)
Purpose: The complex geometry of breast tissue, variable shape, size of breasts, their lack of homogeneity and other organs at risk like the heart and lungs make dose distribution difficult, especially for cases involving large breasts. Assessment of breast dosimetry includes homogeneity dose distribution with complete target coverage and the avoidance of organs at risk as much as possible. The aim of this study is to assess dose distribution and coverage of the target by TLD dosimeter in slab breast phantoms. Methods: This study used a slab anatomical phantom with lung inhomogenity for two different breast sizes, large and small. Exposure was done with 6 MV, utilized PTW reader, oven LTM to annulling conventional methods were carried out with a hand generated contour, 3D treatment planning used RT Dose Plan software. Results: There were areas with lower than 95 percent reference dose in 3D methods decreased in compare of conventional methods. This result for large breasts was remarkable. Received area of target for both size more than 105 percent reference dose reduce to some extent, therefore getting more homogeneity also better coverage for target volume for large breast. Conclusion: This study has shown that conventional methods are not suitable to assessment of dose distribution and coverage in target volume, especially for large breast. Also there was not sufficient dose distribution for small breast a as result of the 3D method, and so can it be useful for crowded hospitals with restricted facility centers because they can use conventional methods with nearly the same results as the 3D method.